Optimalisasi Peran Guru PAI dan Budi Pekerti dalam Pembentukan Karakter Religius dan Moral Siswa di Era Digital - Vernando, Tomi Okta; Junaidi, Isra; Fadriati (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2024)
This study explores the optimization of the roles of Islamic Education (PAI) and character education teachers in fostering students' religious and moral character in the digital era. It highlights the challenges posed by digital technology, which can influence students' values and behaviors. The research emphasizes the necessity for educators to adapt their teaching methods and integrate digital literacy into their curricula. By employing innovative strategies, teachers can effectively instill strong moral values and religious principles, preparing students to navigate the complexities of modern society. This paper concludes that a collaborative effort among educators, parents, and the community is essential for nurturing well-rounded, ethically grounded individuals.